2001
DOI: 10.1163/15685620152691904
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast culture on surface-modified poly (glycolide-co-ε-caprolactone) scaffold for soft tissue regeneration

Abstract: Novel porous matrices made of a copolymer of glycolide (G) and epsilon-caprolactone (CL) (51 : 49, Mw 103000) was prepared for tissue engineering using a solvent-casting particulate leaching method. Poly(glycolide-co-epsilon-caprolactone) (PGCL) copolymer showed a rubber-like elastic characteristic, in addition to an amorphous property and fast biodegradability. In order to investigate the effect on the fibroblast culture, PGCL scaffolds of varying porosity and pore size, in addition to surface-hydrolysis or c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…Kwon et al also studied fibroblast attachment and proliferation on PGCL scaffolds with different pore size range (22–300 μm). They demonstrated that scaffolds with pore size in the range of 150–300 μm supported more adhesion and proliferation of cells . Interestingly, Conde et al did not observed any difference in proliferation as well as odontogenic differentiation of DPSCs on PLLA scaffold with pore size range from 150 to 450 μm .…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…Kwon et al also studied fibroblast attachment and proliferation on PGCL scaffolds with different pore size range (22–300 μm). They demonstrated that scaffolds with pore size in the range of 150–300 μm supported more adhesion and proliferation of cells . Interestingly, Conde et al did not observed any difference in proliferation as well as odontogenic differentiation of DPSCs on PLLA scaffold with pore size range from 150 to 450 μm .…”
Section: Resultsmentioning
confidence: 98%
“…They showed improved hepatic cell adhesion and proliferation as well as albumin secretion . Four studies were also shown that coating of scaffold surface with various materials has impact on cell attachment and proliferation . In studies by Mashhadikhan et al, Koh et al, and Stendahl et al, surface of PLLA scaffolds were coated using gelatin, laminin, and cholesterol segments, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The co-use of these adhesion proteins and biodegradable synthetic polymers enables the construction of cell-adhesive scaffolds for vitally functioning engineered tissues (Almany and Seliktar 2005;Chen et al 2000;Kwon et al 2001;Zhang et al 2005a). Co-electrospinning is a feasible approach to provide a compromise solution for overcoming the shortcomings of synthetic and natural polymers that is producing new porous nanofibrous biomaterials with good biocompatibility and improved mechanical, physical and chemical properties and biological performance.…”
Section: Electrospinningmentioning
confidence: 99%